The Role of Social Innovation in Enhancing the Economic Welfare of Rural Communities - Badriyah, Nurul; Lazuardi, Yanuar; Bakri; Sulaeman, Moh. Muklis (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Social innovation has become one of the key strategies in promoting economic welfare across various regions, particularly in rural communities that often face structural challenges such as poverty, limited access to resources, and low education levels. This study aims to analyze the role of social innovation in improving the economic welfare of rural communities. A qualitative literature review method was employed, utilizing data from articles available on Google Scholar, published between 2018 and 2023. The findings of this study reveal that social innovation plays a highly significant role in enhancing the economic welfare of rural communities. Through collaborative approaches, local empowerment, and the utilization of available resources, social innovation can address various challenges faced by rural communities, such as limited market access, technology, and financing. Case studies, including the village of Nglanggeran in Yogyakarta, sustainable agricultural programs in Central Java, and digital initiatives like "Farmers Go Online," demonstrate that social innovation can create sustainable positive impacts. Social innovation has the potential to be a key driver of inclusive economic growth in rural areas by emphasizing active local community participation and cross-sector collaboration.